APPLICATION OF PHYSICAL EXPERIMENTS IN MODELING AS A STRATEGY FOR DEVELOPING STUDENTS' COGNITIVE ACTIVITY (American Journal of Pedagogical and Educational Research, 2026)
This article examines problem-based instruction as a primary pedagogical strategy for developing and sustaining students’ cognitive activity. The general and specialized functions of problem-based learning are analyzed, and its sequential stages are described. The study investigates techniques for constructing problem situations, the psychological paradoxes inherent in the thinking process, and the mechanisms through which learners solve cognitive problems. Special attention is given to the role of hypothesis formation, group discussion, and reflective practice in deepening conceptual understanding. The findings confirm that problem-based instruction, when systematically implemented, significantly enhances students’ intellectual independence, scientific thinking, and creative competencies.